Chronobiology and Chronotherapy-Related Effects in Non-Traumatic Pain Presentations in the Emergency Department: A Retrospective Study - Akgöl, Jale; Özdinç, Şerife; Karakoca, Serra; Alkan, Bahar Karya; Baş, Melisa; Gündoğdu, Berke Üzeyir; Başaran, Orhan; Çetin, Ferit Suat; Akkuş, Esra; Tanrıkulu, Kaan; Kaya, Zeynep Beyza; Şahin, İsmail and Aras, Mert (The European Research Journal, 2026)
Objectives: Pain is one of the most frequent reasons for emergency department (ED) admissions, yet the chronobiological patterns of pain-related presentations remain insufficiently explored. This study aimed to retrospectively analyze the temporal and seasonal characteristics of non-traumatic pain-related ED visits, with a focus on daily and seasonal variations influenced by circadian rhythms. Methods: This retrospective, descriptive, cross-sectional study included adult patients (≥18 years) who presented to the Afyonkarahisar Health Sciences University Adult ED with non-traumatic pain between January 1, 2023, and December 31, 2023. Cases were identified based on ICD-10 codes for headache (R51, G43, G44), chest pain (R07.1–R07.4), abdominal pain (R10.0–R10.4), and musculoskeletal pain (M54, M79, M25). Demographic data, admission times, diagnostic procedures, treatment initiation, and hospitalization rates were analyzed. Statistical analyses utilized appropriate parametric and non-parametric tests, with significance set at P<0.05. Results: A total of 4524 patients were included (53.9% female; mean age 47.3±21.4 years). Chest pain was the most frequent diagnosis (40%), followed by headache (35.6%), musculoskeletal pain (19.6%), and abdominal pain (4.8%). ED visits peaked in the evening (mode: 21:09) and were least frequent after midnight. Headache admissions were significantly higher in autumn (30.7%), while chest pain was most common in winter (32%). Women more frequently presented with headache and abdominal pain, while men predominantly reported chest and musculoskeletal pain. Conclusions: Non-traumatic pain-related ED visits appeared to follow certain chronobiological patterns with observable sex-related differences. These preliminary findings may contribute to understanding temporal trends in pain-related ED utilization and could serve as a basis for future studies exploring the potential role of chronotherapy in pain management. Validation through larger, multicenter, and prospective studies is needed to strengthen and generalize these findings.